Kajian Komparatif Pemikiran Ekonomi Muhammad Baqir Al-Shadr dan Umer Chapra - Muhammad Firmansyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
This article comparatively examines the economic thought of Muhammad Baqir Al-Shadr and Umer Chapra as two important figures in contemporary Islamic economic discourse. This study employs a qualitative research method with a library research approach, using primary sources consisting of Iqtishaduna by Baqir Al-Shadr, as well as Islam and the Economic Challenge and Toward a Just Monetary System by Umer Chapra. The analysis focuses on the fundamental concepts of Islamic economics, justice and distribution, the role of the state, and approaches to economic reform. The findings indicate that Baqir Al-Shadr views Islamic economics as a normative doctrine derived directly from Islamic law, with an emphasis on pre-production distribution and the strong role of the state as waliyul amr. Meanwhile, Umer Chapra positions Islamic economics as a framework for reforming the modern economic system based on maqashid syariah, emphasizing individual morality, institutional reform, and monetary policy. These differing approaches show that Baqir Al-Shadr’s thought is fundamental and philosophical in nature, whereas Umer Chapra’s thought is implementative and policy-oriented. This article concludes that the two perspectives are complementary in building a just and sustainable Islamic economic system.